Limited Şirkette İntifa Hakkı Sahibi Bağlılık Yükümlülüğüne ve Rekabet Yasağına Tabi Tutulabilir mi? - SOPACI ÖZTUNA, BİRGÜL (My University, 2022)
Türk Ticaret Kanunu’nun 613.maddesinin birinci fıkrasında, limited şirkette ortakların sır saklamakla yükümlü olduğu, ikinci fıkrasında, ortakların şirketin çıkarlarını zedeleyebilecek davranışlarda bulunamayacakları, kendilerine özel menfaat sağlayan, şirketin amacına zarar veren işlemler yapamayacakları ve şirket sözleşmesiyle ortaklar için rekabet yasağı getirilebileceği, düzenlenmiştir. Peki aynı yükümlülükler, pay üzerinde intifa hakkı tesis edilmesi halinde intifa hakkı sahibi için de geçerli olacak mıdır? Bu soruya ilişkin bir düzenleme madde metninde bulunmamaktadır. İntifa hakkı kurulan paylara ilişkin oy hakkının ve oy hakkına bağlı hakların, özellikle bilgi alma ve inceleme hakkının, intifa hakkı sahibi tarafından kullanılabileceği kabul edildiğinde, intifa hakkı sahibi şirket faaliyetlerine, sırlarına vakıf olabilmektedir. Bunun sonucu olarak intifa hakkı sahibinin de şirket ortağı gibi bu bilgileri şirket zararına kullanması, şirketle rekabet oluşturacak faaliyetlerde bulunması tehlikesi mevcuttur. Bu tehlike karşısında açık yasal düzenlemenin olmayışı, uygulamada çıkabilecek ihtilaflar ve açılacak davalar bakımından önemli bir sorun teşkil etmektedir. Bu açıdan yeterince yol gösterici yüksek mahkeme içtihatları da henüz oluşmamıştır. Bu çalışmanın amacı, limited şirkette intifa hakkı sahibinin bağlılık yükümlülüğü ve şirket sözleşmesiyle öngörülmüş rekabet yasağı karşısındaki durumunu tespit ederek, çözüm ortaya koymaktır.

It is regulated in the first paragraph of the article 613 of the Turkish Commercial Code that partners of a limited liability company are obligated to safeguard business secrets, in the second paragraph, it is regulated that partners must refrain from doing anything detrimental to the interests of the company, may not engage in a business bringing them a special advantage, effecting the purpose of the company adversely and that company partners can be prohibited from carrying on any activities in competition with the company with the articles of association. Will the same obligations be applied to the beneficial owners in case beneficial ownership is issued on the share? The article text does not have any regulation on this matter. When it is accepted that the beneficial owner can exercise right to vote regarding to the shares establishing the beneficial right and the rights in connection with the right to vote, especially right to demand information and right to examine, the beneficial owner can be competent on the activities, secrets of the company. Consequently, a beneficial owner, such as a partner, can use the information to the detriment of the company and carry on activities in competition with the company. The lack of any explicit legal regulation causes problems in terms of probable conflicts and lawsuits that may arise in practice. So far, any guiding Supreme Court decision related to this matter has not been given either. The aim of this study is to evaluate the status of the beneficial owner in respect to duty of loyalty and prohibition of competition provided by the articles of association and to create a solution.
Can Beneficial Owners be Subject to the Duty of Loyalty and Prohibition of Competition in Limited Liability Company?
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Ticaret Hukuku; Özel Hukuk; Social Sciences and Humanities; Law; Commercial Law; Private Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Limited Şirket; İntifa Hakkı; Bağlılık (Sadakat) Yükümlülüğü; Bilgi Alma Hakkı; Rekabet Yasağı; Limited Liability Company; Beneficial Ownership; Duty of Loyalty; Right to Information; Prohibition of Competition.